The Real of the Virtual: Critical Reflections on Web 2.0 - Christos Boikos; Konstantinos Moutsoulas; Charalambos Tsekeris (tripleC: Communication, Capitalism & Critique)
Social media, as the heart of Web 2.0, is a relatively novel theoretical notion and social phenomenon, pertaining to a long series of academic subjects, such as digital culture, virtual communication, e-democracy, technological convergence, and online interactivity. Arguably, one of the most useful tools to adequately interpret and analyze this phenomenon is Critical Theory. The present article aims to comprehensively discuss and reflexively elaborate on the complex interrelationship between Critical Theory and Web 2.0 developments. This mainly involves the historicization of the relevant concepts and the identification of crucial sociological, philosophical and interdisciplinary issues that strongly demonstrate the essential ontological complicity between the real and the virtual. In addition, the analytical emphasis on recent social movements, such as the Arab Spring, reflexively depicts the new media as critical media, a characteristic feature that somehow stands in contrast to the participation of the internet in the circulation and accumulation of the Capital. Through contemporary Web’s inherent paradoxes, it is eventually shown that the social potential of the new media can indeed be realised, so that the internet serves the people and the public good.